Checklist of freshwater periphytic diatoms in the midstream of Brantas River, East Java, Indonesia - Endang Masithah; R. ADHARYAN ISLAMY (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Masithah ED, Islamy RA. 2023. Checklist of freshwater periphytic diatoms in the midstream of Brantas River, East Java, Indonesia. Biodiversitas 24: 3269-3281. Periphytic diatoms are a group of microalgae that live attached to the surface of the substrate such as rocks, aquatic plants, or other objects in the water. This group has potential as an indicator of environmental quality of water because its existence is influenced by water quality, such as nutrient levels and pollution levels. They are also useful in describing the ecological state, performances, and sustainability of ecosystems because of their ability to measure various environmental parameters and correlate them with diversity, evenness, and richness. This study provides a checklist of freshwater periphytic diatoms in the midstream of Brantas River, East Java, Indonesia. The sampling and identification according to published methods were carried out at the Laboratory of Aquaculture, Faculty of Fisheries and Marine, Universitas Airlangga, Surabaya. This study was undertaken once a week in a month (May 2022) between 9 a.m. and 1 p.m. (GMT + 7). Determination of sampling sites based on differences in land use. Sampling site 1 is located at the Kedungkandang Dam, sampling site 2 is located at the Waterfall Amprong tourist area, sampling site 3 is located at the river branch below the Kedungkandang bridge, and sampling site 4 is located in a residential and agricultural area. The total abundance of freshwater periphytic diatom ranges from 938,905 Ind/mm2 - 1,597,758 Ind/mm2. The lowest total abundance is at station 1 with a value of 938,905 Ind/mm2 and consists of 17 genera. The highest total abundance is at station 4 with a value of 1,597,758 Ind/mm2 and consists of 17 genera. In this study, 27 genera were found spread across 3 phylum.